Nocardia infection in AIDS: a clinical and microbiological challenge. Issue 9 (September 1992) - Coker, R J; Bignardi, G; Horner, P; Savage, M; Cook, T; Tomlinson, D; Weber, J
Abstract : A case of Nocardia asteroides pneumonia was diagnosed after death in a patient with AIDS. Six sputum cultures and one bronchoalveolar lavage fluid contained no pathogens, and no growth was obtained from one pleural fluid aspirate. None of these specimens was incubated for more than two days. Extended incubation for mycobacteria also failed to help in the diagnosis. N asteroides was isolated from pus taken from the lung cavity during the post mortem examination. It is suggested that if nocardiosis enters the differential diagnosis all specimens should be cultured for at least two weeks and the use of selective media be considered. This case highlights the need for clinicians to maintain a high index of suspicion for this pathogen.